1998
DOI: 10.1097/00005537-199805000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Orbital Blow‐out Fractures With Nasoseptal Cartilage

Abstract: The goals of reconstruction in orbital blow-out fractures are to restore floor continuity, provide support of orbital contents, and prevent fibrosis of soft tissues. Although ease of use has popularized alloplasts, autogenous material provides greater biocompatibility and results in low rates of infection, extrusion, and migration. Nasoseptal cartilage is an easily accessible, abundant, autogenous source that provides support to the orbital floor and minimal donor site morbidity. Thirteen patients who presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…As an autogenic material, they also have other advantages, such as biocompatibility and lower complication rates, in addition to their superior qualities. 8 Kraus et al have also reported successful results in this field using septal cartilage in children 19 and adults. 18 Conchal cartilage, which possesses characteristics and advantages similar to those of cartilage grafts, was used formerly in orbital reconstruction.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As an autogenic material, they also have other advantages, such as biocompatibility and lower complication rates, in addition to their superior qualities. 8 Kraus et al have also reported successful results in this field using septal cartilage in children 19 and adults. 18 Conchal cartilage, which possesses characteristics and advantages similar to those of cartilage grafts, was used formerly in orbital reconstruction.…”
Section: Discussionmentioning
confidence: 98%
“…Lai et al, 8 who proposed the superiority of autogenic materials, have also reported favorable results in the repair of orbital blowout fractures in which they have used nasoseptal cartilage. The authors report that nasoseptal cartilage, although it is rarely used in this field, possesses the advantages of having a greater survival rate and a lower rate of resorption because of its anaerobic metabolism, because of its being close to the surgical location to harvest, and because of its having minimal cosmetic and functional morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nasal septum is advantageous owing to the rapid harvest time and the minimal cosmetic and functional morbidity. [17,18] Bayat et al [19] performed a randomized clinical trial and found a superior effect for nasal cartilage compared to conchal cartilage with respect to the incidence of enophthalmos at the 3-6 months follow-up point. Whereas, the autologous cartilage still cannot avoid donor site morbidity and is limited in quantity.…”
Section: Biomaterialsmentioning
confidence: 99%
“…14 The nasal septum is particularly advantageous because of the rapid harvest time and the minimal cosmetic and functional morbidity. 15 Bayat et al 16 performed a randomized clinical trial (RCT) and found a superior effect for nasal cartilage versus conchal cartilage with respect to the occurrence of enophthalmos at the 3-6-month follow-up. A second RCT found no significant differences in the clinical outcomes of orbital fractures repaired with either a cartilage graft or an absorbable polyacid co-polymer.…”
mentioning
confidence: 99%